The Effects of Preharvest Mild Shading on the Quality and Production of Essential Oil from Kaffir Lime Leaves (Citrus hystrix) - Budiarto, Rahmat; Poerwanto, Roedhy; Santosa, Edi; Efendi, Darda; Agusta, Andria (Journal of Tropical Crop Science, 2022)
Kaffir lime (Citrus hystrix DC) is a less popular citrus species commonly used as a food spice and a source of essential oil. Early studies report the success of preharvest mild shading to increase leaf yield, although there is still limited information on the effect of preharvest shading on the quality of essential oil produced. The aim of this current study is to evaluate the effect of preharvest mild shading factors on the yield, physical characteristics, and metabolite fingerprinting of kaffir lime leaves essential oil (KLLEO). One-year-old kaffir lime trees were sampled in two preharvest treatments, i.e., open sun and mild shading (24% light reduction) at Pasir Kuda experimental field, Bogor, Indonesia. Statistical analysis showed that there was no significant effect of preharvest treatment on yield and physical characteristics (color, specific gravity, and refractive index) of KLLEO. In contrast, there was a metabolite fingerprinting variation of KLLEO as an effect of mild shading. The relative percentage of bergamol, citronellol, caryophyllene oxide, citronellic acid, isopulegol, isopulegyl formate, limonene, linalool, and linalool oxide was increased by mild shading. On the other hand, the main metabolite (citronellal) was significantly reduced by about 10% in shading treatment, as compared to the open-sun ones.